2013
DOI: 10.1063/1.4801904
|View full text |Cite
|
Sign up to set email alerts
|

Mask assisted fabrication of nanoislands of BiFeO3 by ion beam milling

Abstract: We report on a low-damage method for direct and rapid fabrication of arrays of epitaxial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Recently, Morelli et al [27] fabricated BFO nanoislands by template-assisted FIB method based on epitaxial BFO thin films grown on SrTiO 3 (100) substrates. Arrays of 45 nmthick aluminium dots were first evaporated on BFO thin films through template with aperture diameter of 400 nm.…”
Section: Focus Ion Beam (Fib) Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Morelli et al [27] fabricated BFO nanoislands by template-assisted FIB method based on epitaxial BFO thin films grown on SrTiO 3 (100) substrates. Arrays of 45 nmthick aluminium dots were first evaporated on BFO thin films through template with aperture diameter of 400 nm.…”
Section: Focus Ion Beam (Fib) Millingmentioning
confidence: 99%
“…By using the top-down approach such as FIB milling method, Morelli et al [27] fabricated the arrays of epitaxial BFO islands with flat top surfaces and lateral sizes down to 250 nm by starting from a continuous BFO thin film. PFM images showed that the as-fabricated BFO nanoislands preserved ferroelectric properties with switchable polarization and exhibited retention of polarization state at least for several days.…”
Section: Bfo Nanoislandsmentioning
confidence: 99%
“…In this way the material is removed where the layer is not present, therefore producing defined islands without utilization of high-energy beam [51].…”
Section: Mask-assisted Fib Millingmentioning
confidence: 99%
“…Timeline of significant results from FIB processing of ferroelectrics. Adapted with permission from (in chronological order): Ganpule, Stanishevsky et al; Bühlmann, Dwir et al; Nagarajan, Stanishevsky et al; Nagarajan, A. Roytburd et al; Chu, Martin et al; Rémiens, Liang et al; McQuaid, McGilly et al; Schilling, Prosandeev et al; Morelli, Johann et al; Whyte, McQuaid et al; Whyte and Gregg …”
Section: Introductionmentioning
confidence: 99%